Krótkookresowe sposoby zarządzania finansami a poziom kapitału obrotowego netto na przykładzie wybranych przedsiębiorstw branży budowlanej: The short-term ways of the management of finances in comparison with the level of the net working capital through the examples of selected building enterprises - Słowik, Dorota (Management and Administration Journal, 2021)
This article features issues concerning the management of the current assets, the current liabilities and the working capital. The problems of the short-term management of finances are shown using examples of 19 firms of the building trade.In the period of 2006 – 2010 mentioned firms attained an average income above 100 000 000 zlotys. The results of the analysis show that 6 enterprises, among all studied firms did not change the company policy within the scope of managementof the current assets and the current liabilities. Regardless of the applied management model, the enterprises had a positive value of the net working capital.